Intellectual property : valuation, exploitation, and infringement damages. - Parr, Russell L.; Caire, Yuridia (John Wiley & Sons, Inc., 2022)
Stay informed about every major and recent development in the law of intellectual property in the US In the 2022 Cumulative Supplement to the 5th edition of Intellectual Property: Valuation, Exploitation, and Infringement Damages, a renowned team of authors delivers a comprehensive and authoritative review of the most relevant and impactful changes to the legal regime governing intellectual property in the United States. Current to the year 2022, the Supplement explores the legislative and regulatory changes, as well as major developments in case law, affecting intellectual property in the US. An indispensable update for lawyers advising founders, entrepreneurs, and executives in any industry, and business leaders themselves, this volume is a one-stop resource covering every applicable recent change in a rapidly evolving area of the law.